Structural, electronic, and magnetic properties of quasi-1D quantum magnets [Ni(HF2)(pyz)2]X (pyz = pyrazine; X = PF6(-), SbF6(-)) exhibiting Ni-FHF-Ni and Ni-pyz-Ni spin interactions. - Manson, J; Lapidus, S; Stephens, P; Peterson, P; Carreiro, K; Southerland, H; Lancaster, T; Blundell, S; Steele, A; Goddard, P; Pratt, F; Singleton, J; et al. (2011)
[Ni(HF(2))(pyz)(2)]X {pyz = pyrazine; X = PF(6)(-) (1), SbF(6)(-) (2)} were structurally characterized by synchrotron X-ray powder diffraction and found to possess axially compressed NiN(4)F(2) octahedra. At 298 K, 1 is monoclinic (C2/c) with unit cell parameters, a = 9.9481(3), b = 9.9421(3), c = 12.5953(4) Å, and β = 81.610(3)° while 2 is tetragonal (P4/nmm) with a = b = 9.9359(3) and c = 6.4471(2) Å and is isomorphic with the Cu-analogue. Infinite one-dimensional (1D) Ni-FHF-Ni chains propagate along the c-axis which are linked via μ-pyz bridges in the ab-plane to afford three-dimensional polymeric frameworks with PF(6)(-) and SbF(6)(-) counterions occupying the interior sites. A major difference between 1 and 2 is that the Ni-F-H bonds are bent (∼157°) in 1 but are linear in 2. Ligand field calculations (LFT) based on an angular overlap model (AOM), with comparison to the electronic absorption spectra, indicate greater π-donation of the HF(2)(-) ligand in 1 owing to the bent Ni-F-H bonds. Magnetic susceptibility data for 1 and 2 exhibit broad maxima at 7.4 and 15 K, respectively, and λ-like peaks in dχT/dT at 6.2 and 12.2 K that are ascribed to transitions to long-range antiferromagnetic order (T(N)). Muon-spin relaxation and specific heat studies confirm these T(N)'s. A comparative analysis of χ vs T to various 1D Heisenberg/Ising models suggests moderate antiferromagnetic interactions, with the primary interaction strength determined to be 3.05/3.42 K (1) and 5.65/6.37 K (2). However, high critical fields of 19 and 37.4 T obtained from low temperature pulsed-field magnetization data indicate that a single exchange constant (J(1D)) alone is insufficient to explain the data and that residual terms in the spin Hamiltonian, which could include interchain magnetic couplings (J(⊥)), as mediated by Ni-pyz-Ni, and single-ion anisotropy (D), must be considered. While it is difficult to draw absolute conclusions regarding the magnitude (and sign) of J(⊥) and D based solely on powder data, further support offered by related Ni(II)-pyz compounds and our LFT and density-functional theory (DFT) results lead us to a consistent quasi-1D magnetic description for 1 and 2.